2017
DOI: 10.1016/j.expneurol.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted human glial-restricted progenitors can rescue the survival of dysmyelinated mice independent of the production of mature, compact myelin

Abstract: The therapeutic effect of glial progenitor transplantation in diseases of dysmyelination is currently attributed to the formation of new myelin. Using magnetic resonance imaging (MRI), we show that the therapeutic outcome in dysmyelinated shiverer mice is dependent on the extent of cell migration but not presence of mature and compact myelin. Human or mouse glial restricted progenitors (GRPs) were transplanted into rag2−/− shiverer mouse neonates and followed for over one year. Mouse GRPs produced mature myeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 44 publications
6
66
1
Order By: Relevance
“…Conversely, human GPs at the same time point had already migrated extensively away from the transplantation site, and were present within the entire brain, including white matter and grey matter areas. No production of compact myelin could be detected by histology, which was confirmed by the MRI findings (Lyczek et al, 2017). This study thus revealed that an extensive migration and distribution of GPs within the entire brain is a pre-requisite to achieve the therapeutic effect ( Figure 1).…”
Section: Th Er a P Eu Ti C P Oten Ti A L Of Gp Ssupporting
confidence: 66%
See 3 more Smart Citations
“…Conversely, human GPs at the same time point had already migrated extensively away from the transplantation site, and were present within the entire brain, including white matter and grey matter areas. No production of compact myelin could be detected by histology, which was confirmed by the MRI findings (Lyczek et al, 2017). This study thus revealed that an extensive migration and distribution of GPs within the entire brain is a pre-requisite to achieve the therapeutic effect ( Figure 1).…”
Section: Th Er a P Eu Ti C P Oten Ti A L Of Gp Ssupporting
confidence: 66%
“…While no post-mortem studies from these patients were reported, the MRI data added an interesting clue. A widespread improvement of MRI parameters in the white matter, as found in the preclinical study by Lyczek et al (Lyczek et al 2017), was not observed (Gupta et al 2012). Only a few small hypointensities indicative of potential myelination were observed, which could correspond to the sites of cell injections.…”
Section: Therapeutic Potential Of Glial Progenitors (Gps)mentioning
confidence: 91%
See 2 more Smart Citations
“…The role of glial progenitors and transplantation is critically important due to their proven role in rescuing myelination phenotype in mice. [14][15][16] NSCs play pivotal roles in everything from infection to psychiatric disorders. Multiple studies from our lab have utilized these hNSC culture and differentiation techniques to improve efficacy of stem cell transplantation in the context of traumatic brain and spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%